The Potential of Using Augmented Reality (AR) Technology as Learning Material in TVET - Ab Halim, Fazlinda; Wan Muda, Wan Hanim Nadrah; Zakaria, Normah; Binti A. Samad, Nur Hanifah (Journal of Technical Education and Training, 2019)
In the field of education today, people can choose from a variety of ways and methods to acquire specific information and skills; here are some good examples: classroom lectures with textbooks, computers, hand-held devices, and other electronics appliances such as tablets and smartphones. In a rapidly changing society, there are countless sources of knowledge and a great deal of available information; hence, adopting an appropriate method and applying relevant information at the right time and place are important in both schools and business settings. The augmented reality (AR) technology is one of the most advanced developments in the education sector tailored for 21st Century learning. With so much to offer, it is worthwhile to investigate the potential of integrating AR into the teaching-learning processes. This study focuses on exploring the possibility of merging TVET learning materials with the AR technology; the survey was carried out among the lecturers to gauge their knowledge and perception of AR as well as the relationship between the two elements. This quantitative study includes randomly selected samples of 230 lecturers from Universiti Tun Hussein Onn Malaysia (UTHM). The respondents were given a questionnaire to answer. The SPSS version 22 software package was used to analyse the data collected. Overall, the mean score indicates that the lecturers' knowledge level for AR technology is high. The lecturers also have a positive perception of using AR as a tool to incorporate and present the learning materials. Finally, this study discovers that there is a positive relationship between the lecturersâ€™ information about AR and their perception of using AR as a vehicle to deliver the learning materials. AR is expected to achieve widespread adoption in schools, universities and colleges,  TVET and other higher learning institutions. Therefore, this study may be useful to the developers and providers of augmented reality solutions, end users of these solutions, teachers and students, and the experimenting digital communities.